IoT-based pesticide distribution control system with photometric sensor frameworkIoT-based pesticide distribution control system with photometric sensor framework - Al Hakim, Rosyid R; Islami, Ichsani Nurul; Ropiudin; Pangestu, Agung; Jaenul, Ariep; Arief, Yanuar Z.; Hidayah, Hexa Apriliana (Journal of Global Engineering Research and Science, 2022)
The use of pesticides is often given under extreme conditions. The excess use of these pesticides can harm both the farmers directly and the affected environment; this is the impact of the uncontrolled use of pesticides. There is a need for a control system to control the distribution of pesticides on agricultural land. This article seeks to provide a control system design for controlling the distribution of pesticides by utilizing photometric technology integrated with the internet of things (IoT). The control system is designed automatically with a sensing system or an operating record. It is expected to be able to disseminate the correct use of pesticides to achieve production efficiency. This study provides a design of an automatic control system for pesticide distribution IoT-based. We use a photometric sensor to control the pesticide distribution. Future work can be implemented for prototype work due to smart farming to control pesticide distribution automatically.